The Postoperative Changes of Nasal Septum and Maxilla After Alveolar Bone Grafts in Patients With Unilateral Alveolar Cleft. Issue 3 (May 2020) - Kim, Jeenam; Jun, Dongkeun; Lee, Myungchul; Shin, Donghyeok; Kim, Soonheum; Jo, Dongin; Kim, Cheolkeun; Choi, Hyungon
Abstract : Background: Alveolar clefts give rise to many aesthetic and functional problems among affected patients. Therefore, surgical adjustments of the bony defective anomalies are important. The authors performed secondary bone grafts and analyzed the effects particularly on the nasal septum and maxillary area (midface). Methods: The patients who had alveolar bone grafts were retrospectively reviewed with pre/postoperative 3-dimensional computed tomography; the measurements included distances between the anterior nasal spine (ANS) and the vertical midline, angles between the nasal septum and the transverse line, and angles between the floor of the pyriform aperture and the transverse line. Results: A total number of 23 patients were finally included in the study. The mean age of the patients was 9.7 ± 1.95 years (range, 7–14 years). The mean distance between the ANS and the vertical midline was 5.3 ± 4.70 mm/4.9 ± 4.15 mm pre/postoperatively, showing the mean paired difference of 0.4 ± 0.89 mm ( P < 0.05). The mean angles between the nasal septum and the transverse line and between the floor of the pyriform aperture and the transverse line were 64.5 ± 14.69°/65.9 ± 13.73° and 21.7 ± 8.94°/11.5 ± 7.03° pre/postoperatively, showing the mean paired differences of −1.4 ± 2.78° and 10.1 ± 8.20°, respectively (both P < 0.05). Conclusion: The results suggest that secondary alveolar bone grafting has expanded effects on the adjacent midfacial structures. Abstract : Supplemental Digital Content is available in the text